Beyond Logframe: Critique, Variations and Alternatives - Hummelbrunner, Richard (Beyond Logframe; Using Systems Concepts in Evaluation, 2010)
Over the last decades, the Logical Framework Approach (LFA) has become universally known and has assumed a key role for planning and managin g development interventions. LFA, however, is not uncontroversial and the approach has been subject to criticism, concerning both its theore tical foundations and practical use. Despite these criticisms LFA’s po sition has not been fundamentally weakened and while many donors ackno wledge its limits and weaknesses, they maintain (some would say impose ) its use as a planning and monitoring tool. This chapter reviews some of the experience gained with LFA and outlines major attempts to deve lop variations – or move beyond it altogether. The first section brief ly describes the LFA concept and summarizes the main points of critiqu e. Section 2 then explores some variations which have been developed i n response to this critique and to improve LFA as a management tool. S ection 3 proposes a systemic alternative to logframe and Section 4 out lines alternatives to LFA which have recently been introduced in Germa n development aid.